Urinary incontinence in women - the overview of pharmacological and surgical methods - Mikut, Karolina; Wijata, Aleksandra; Gorajek, Anna; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work: Urinary incontinence (UI) is a common problem among women and the incidence increases with age. It is estimated that about 50% of women will be affected by this problem. There are 5 types of urinary incontinence: exercise, pressure, mixed, overflow and functional. Stress UI is the most common cause among young women, while stress UI is the second most common cause among older women. The widespread use of this phenomenon makes it a significant economic burden. State of knowledge (brief description): Due to the different types of UI and its many causes, treating this disorder becomes a significant challenge. It is important to use combination therapy, starting with pelvic floor muscle strengthening exercise, lifestyle modification, weight loss, and smoking cessation, followed by drug therapy and surgery as necessary. Summary: Currently, many drugs are used in the treatment of urinary incontinence, with different mechanisms of action, which allow the treatment of various types of UI, but pharmacotherapy often does not bring the expected benefits. Surgical treatment appears to be a promising form of treatment, but more research is needed on the long-term effects.